Analysis of Community Understanding of Interest (Riba) and Its Influence on Borrowing Interest in Non-Bank Financial Institutions in Padang Bindu Village, Pasemah Air Keruh District, Empat Lawang Regency - Viana Retno Pinaseh; Yossy Arisandy; Makmur (International Journal of Business and Quality Research, 2026)
This study aims to examine public understanding of interest (riba) and its influence on the intention to borrow from non-bank financial institutions in Padang Bindu Village. This research employs a qualitative method with a phenomenological approach. Data collection techniques include interviews, observations, and documentation involving informants consisting of community members who have taken loans and representatives of non-bank financial institutions. Data analysis uses the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that the community generally understands that riba refers to an additional charge in loans prohibited in Islam; however, this understanding remains general and not in-depth. Furthermore, such understanding does not significantly influence people's interest in borrowing. This is mainly due to urgent economic needs, ease of loan procedures, and social environmental influences. Additionally, some community members perceive that small amounts of interest are still acceptable. Thus, public understanding of riba has not fully influenced their financial decision-making behavior.